Death in Beijing: Alma M. Karlin’s Description of Chinese Funerary Rituals and Mourning Practices - Vampelj Suhadolnik, Nataša (Poligrafi, 2019)
Alma Maximiliane Karlin (1889–1950) was a world traveller, writer, journalist, and collector from Slovenia. She embarked on an eight-year journey around the world in November 1919, in the course of which she published a series of travel sketches in the Cillier Zeitung, a local German-language newspaper. In one of these she reported on funerary rituals and mourning practices in China. After returning to Europe, she was to cover the same topic in her three‑volume travelogue, published between 1929 and 1933. In this paper we analyse these two early accounts of Chinese funerary rituals by Alma Karlin. We also consider some material objects linked to mortuary rites and ancestor worship that she brought back from her voyage in order to gain a broader understanding of her views on Chinese attitudes towards the dead. Supported by a close reading of material and textual sources on Chinese funeral practices, we compare her treatment of the subject with other accounts written by Slovenian missionaries to China in the early twentieth century. In addition to discussing certain personal elements in these accounts, we attempt to place them in their socio‑historical context.